Synthesis Of Chitosan From Lobster (Nephropidae) Shell Using Reflux Heating Method - Aminati, Salmah; Brilliany, Rhaina Annadroh; Dini Aprilia , Segi Tasya; Arini, Regita Putri; Warahmah, Siti Aisyah Mawaddah; Cahayaningsih, Ananda Capriyati (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2025)
Chitosan synthesis from lobster shell waste (Neurophidae) has been carried out using a conventional heating method using reflux. The synthesis of chitin into chitosan was carried out by demineralization using a 5% (v/v) HCl solution, followed by a deproteination process using a 3.5% NaOH solution with a ratio of 1:10 (w/v) until chitin was formed. The chitin formed was then deacetylated using a 40% (w/v) NaOH solution until chitosan was formed. Analysis of the synthesized chitin and chitosan included confirmation of the FTIR spectra, as well as determining the degree of deacetylation of chitosan. The characterization results showed that lobster shell waste can be synthesized into chitosan using a conventional heating method at a temperature of 50-70 °C for 1 hour. The chitosan formed had a degree of deacetylation of 73.92%. Meanwhile, the yield of chitin was 35% and the yield for chitosan was 13%.